A harmonics detection method based on improved comb filter of sliding discrete Fourier for grid-tied inverter. (December 2020) - Chen, Dongdong; Lin, Yanqiang; Xiao, Long; Xu, Zhenming; Lian, Hemiu
Abstract: Harmonic detection plays an important role in power quality for grid-tied inverters. Among the various methods, sliding discrete Fourier transform (SDFT) based algorithms have found wide and popular applications due to advantages like simplicity and excellent selectively filtering properties. However, SDFT suffers from disadvantages like slow dynamics and large memory occupation. In this paper, the discrete transfer function of SDFT harmonic extraction method is analyzed, and the SDFT transfer function is divided into three parts: comb filter, resonance controller, and adjustment factor. It is found that the comb filter determines the harmonic component that SDFT needs to detect and the dynamic performance of SDFT. Thus, the comb filter can be improved according to the characteristics of the load current, thereby achieving faster dynamic performance while reducing the digital storage space required for the implementation of the SDFT algorithm. Therefore, a general harmonics detection is proposed, which could detect harmonics by adjusting the comb filter of SDFT according to the characteristics of the load current. Finally, the correctness and effectiveness of the proposed general harmonics detection method are verified by relevant experiments.